Child trauma and attachment in common sense and doodles a practical guide - Silver, Miriam 1974- (London Philadelphia Jessica Kingsley Publishers, 2023)
"Trauma and attachment are commonly used terms, but are complex concepts. 'Trauma' refers to negative experiences that cause us to fear for our safety, whilst 'attachment' describes meaningful relationships with someone we love or respect. Why, then, is so much of the language surrounding these concepts so obscure, and why is it so challenging to help children who have experienced trauma, and lack healthy attachment bonds? Providing grounded advice accompanied by accessible 'doodles' throughout, this guide aims to bring some clarity to the subject. It explains the differing attachment patterns in children who are adopted, fostered, or have experienced early trauma. The book also provides advice on how to repair attachment difficulties and to build secure, loving relationships. With new material on cultural diversity and sexual exploitation as well as specific guidance for trafficked and asylum-seeking children, this fully updated new edition provides you with all you need to know."--Publosher's website.
Includes bibliographical references (pages 225-231) and index.
Keywords: Attachment behavior in children; Post-traumatic stress disorder in children; Abused children -- Psychology; Adopted children -- Psychology